Ubuntu as an Experience of Bantu African Humanism (Devenires, 2013)
This article aims to show that Ubuntu is an experience of African humanism. This concept is based on a Zulu (South African ethnic group) saying: “Ubuntu ngumuntu ngabantu”, that means “the person becomes human through other people”, or “I am because we are.” This view settles the community as a place of realization of the human. That means that the human being is done when he relates to other human beings. So the relationship becomes the nature of Muntu (person), becomes his reality. That stresses the relational ontology that considers every human being as a subject because is always interacting with other beings (human, animate and inanimate), thereby affecting the society in which he lives.